Integrating Ki Hadjar Dewantara’s values in learning modules in elementary schools: Analysis of teacher and student needs - Setyaningsih, Setyaningsih; Hidayatullah, Furqon; Asrowi, Asrowi; Rahman, Abdul (Edelweiss Applied Science and Technology, 2024)
This research investigates the significance of implementing Ki Hadjar Dewantara’s values in elementary schools as a strategy to mitigate bullying, which has a considerable negative impact on students both socially and academically. This study aimed to identify the needs of teachers, students, and school principals in developing an effective educational module that incorporates these values. Employing a qualitative research design, data were collected through guided written reflections, in-depth interviews, passive observations, and document analyses across four public elementary schools in Surakarta. The data were analyzed using triangulation for validation and thematic analysis to identify the key patterns and themes. The findings indicate that principles such as "Ing ngarsa sung tulada," "Ing madya mangun karsa," and "Tut wuri handayani" Tut wuri handayani are recognized within the curriculum; however, their application remains inconsistent and lacks focus. This underscores the necessity of a structured and culturally relevant module that can integrate these values into daily classroom activities. The study concludes that a well-developed module can enhance academic learning while significantly reducing bullying and strengthening students’ character. These findings suggest that the module should be designed to support student-centered learning, utilize interactive approaches, and leverage technology. Further research is required to assess the long-term effectiveness of this module in a broader context.